Autopercepção do ponto de constrição da língua nas fricativas alveolares em mulheres jovens com posicionamento de língua normal e alterado - Abreu, Ana Clara Varella [UNESP]; Gurgel, Júlio de Araújo [UNESP]; Rodrigues, Luciana Lessa; Genaro, Katia Flores; Avelar, Débora Dos Santos [UNESP]; Chagas, Eduardo Federighi Baisi; Marino, Viviane Cristina de Castro [UNESP] (FapUNIFESP (SciELO), 2021)
PURPOSE: This study investigated the self-perception of 49 women, monolingual speakers of Brazilian Portuguese, about their tongue position for the alveolar articulation of the fricatives [s] and [z]. METHODS: The video recording of speech samples of these 49 women (ages 18 to 28) were analyzed by three Speech-Language Pathologists. They were classified into two groups: Group 1 (G1, n=25), with no alterations in the tongue position during the production of [s] and [z], and Group 2 (G2, n=24), with alterations in the tongue position during the production of [s] and [z]. The tongue position self-perception experiment required the participants to identify the specific tongue constriction point in the production of [s] and [z] (apical, laminal, or other) during the reading of 24 words and 24 pseudowords. The Friedman test, with posterior paired comparisons, was used for the intragroup analysis. The Mann-Whitney test was used for intergroup comparisons. The statistical significance adopted was 5% (p<0.05). RESULTS: G1 reported apical and laminal tongue constrictions while GE reported these constrictions plus other tongue adjustments. The presence of other tongue adjustments differentiated the groups, G1 and G2 (p=0,002). There were significant differences between [s] and [z] for G1, with the laminal position occurring more often in [s] compared to [z]. CONCLUSION: Women with and without alteration in the tongue position reported apical and laminal constrictions. Howerer, other tongue adjustments were self-perceived in the presence of altered tongue position.

OBJETIVO: Investigar a autopercepção do ponto de constrição da língua na produção de [s] e [z] por jovens monolíngues com posicionamento de língua normal e alterado. MÉTODO: Três fonoaudiólogas analisaram gravações de fala em vídeo de 49 mulheres, com idades entre 18 e 28 anos (média=20 anos e 7 meses), classificando-as em: Grupo 1, (G1, n=25), com ausência de alterações no posicionamento de língua na produção de [s] e [z] e Grupo 2 (G2, n=24), com alterações no posicionamento de língua nestes fones. A autopercepção do ponto de constrição da língua foi investigada questionando cada jovem sobre o local em que sua ponta da língua encostava (apical, laminal ou “outros ajustes”) ao produzir [s] e [z] na leitura de palavras e pseudopalavras. O teste de Friedman, com comparações par a par posteriores, foi utilizado para análise intragrupo. O teste de Mann-Whitney foi utilizado para as comparações entre grupos. Adotou-se nível de significância de 5%. RESULTADOS: Em G1 houve relatos de ponto de constrição apical e laminal enquanto em G2 houve estes relatos, e também de outros ajustes de língua. A presença de outros ajustes da língua diferenciou G1 e G2 (p=0,002). Em G1, houve diferença significativa entre [s] e [z], sendo que o ponto laminal ocorreu com mais frequência em [s] do que em [z]. CONCLUSÃO: Jovens com posicionamento de língua normal e alterado relataram pontos de constrição da língua apical e laminal em fricativas alveolares. Porém, outros ajustes de língua foram percebidos diante de posicionamento de língua alterado.
Self-perception of tongue tip constriction in alveolar fricatives produced by young women with and without normal tongue positioning